2015
DOI: 10.1002/hed.24044
|View full text |Cite
|
Sign up to set email alerts
|

Orbital carcinomas treated with adjuvant intensity‐modulated radiation therapy

Abstract: Favorable disease control rates for orbital carcinomas are achievable with IMRT after orbital exenteration even for patients with advanced disease. Toxicity for the contralateral eye was minimal. © 2015 Wiley Periodicals, Inc. Head Neck 38: E580-E587, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Furthermore, patients with lacrimal gland tumors achieved 2-year LPFS and RRFS rates of 100 and 88.9%, respectively, although ~ 40% had T4 disease. Our results mimicked the most favorable 2-year outcome in terms of survival and local control despite of a less favorable clinical presentation [21, 24, 26, 27].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, patients with lacrimal gland tumors achieved 2-year LPFS and RRFS rates of 100 and 88.9%, respectively, although ~ 40% had T4 disease. Our results mimicked the most favorable 2-year outcome in terms of survival and local control despite of a less favorable clinical presentation [21, 24, 26, 27].…”
Section: Discussionsupporting
confidence: 73%
“…Three- or 5-year LPFS rates of 60~65% [21, 23], with similar OS rates of 60% have been reported. In a more recently published series, adjuvant IMRT after exenteration produced a 3-year LPFS and OS rates of 91 and 70%, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
“…Most postoperative radiotherapy is conformal radiotherapy. 5,6 This study reported the outcome and toxicity for ACCHN patients treated by surgery combined with intensity modulated conformal radiotherapy (IMRT) in a single institute.…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive orbital malignant tumors are also treated with orbital exenteration because of the complexity of the surrounding anatomy. 3 , 9 , 10 In recent years, a multidisciplinary orbit‐sparing treatment approach is generally recommended when feasible to preserve some extent of visual function while maintaining high rates of local control. 9 In a study of 29 locally advanced orbital malignant tumors, favorable oncological outcomes with a 5‐year survival rate of 60% and 5‐year local control rate of 83% were achieved by applying postoperative IMRT following orbital debridement.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of achieving local control must be weighed against the toxicities and long‐term effects of treatments, which can result in significant morbidity, such as ipsilateral loss of vision and/or poor cosmetic impact. 3 Several recent studies have reported favorable oncological outcomes in patients with orbital malignant tumors treated with skull base surgery followed by adjuvant intensity‐modulated radiotherapy (IMRT) 3 , 4 , 5 or particle radiotherapy. 6 However, the roles of skull base surgery and particle radiotherapy have not been fully investigated due to its rarity and variety of histological types.…”
Section: Introductionmentioning
confidence: 99%